Integrasi Teknologi dan Transparansi Digital dalam Sistem Pembiayaan Pendidikan Modern - Kasno Kasno; Casmadi Casmadi; Sutrisno Sutrisno (STIT Ahlussunnah Bukittinggi, 2026)
This study aims to examine the integration of technology and digital transparency in modern education financing systems and its implications for financial management effectiveness and educational service quality. This study adopts a qualitative literature review approach. Data were collected from scholarly publications, educational regulations, and relevant policy documents and analyzed using thematic content analysis to identify key themes related to technology integration and digital transparency in education financing systems. The findings reveal that technology integration enhances the efficiency, accuracy, and accountability of education financing through the implementation of financial information systems, digital reporting platforms, and technology-based budgeting mechanisms. Digital transparency strengthens information disclosure, public oversight, and stakeholder trust in educational institutions. Furthermore, the synergy between technological innovation and transparent governance supports more strategic and accountable resource allocation, contributing to improved educational service quality. The study implies that digital transformation in education financing is not merely an administrative innovation but also a strategic framework for strengthening transparent, adaptive, and sustainable educational governance.